Similar local, but different systemic, metabolomic responses of closely related pine subspecies to folivory by caterpillars of the processionary moth - Rivas-Ubach, A; Sardans, J; Hódar, J A; Garcia-Porta, J; Guenther, A; Oravec, M; Urban, O; Peñuelas, J (Plant biology (Stuttgart, Germany), 2016)
Plants respond locally and systemically to herbivore attack. Most of the research conducted on plant-herbivore relationships at element and molecular levels have focused on the elemental composition or/and certain molecular compounds or specific families of defence metabolites showing that herbivores tend to select plant individuals or species with higher nutrient concentrations and avoid those with higher levels of defence compounds. We performed stoichiometric and metabolomics, both local and systemic, analyses in two subspecies of Pinus sylvestris under attack from caterpillars of the pine processionary moth, an important pest in the Mediterranean Basin. Both pine subspecies responded locally to folivory mainly by increasing relative concentrations of terpenes and some phenolics. Systemic responses differed between pine subspecies, and most of the metabolites presented intermediate concentrations between those of the affected parts and unattacked trees. Our results support the hypothesis that foliar nutrient concentrations are not a key factor for plant selection by adult female processionary moths for oviposition, since folivory was not associated with any of the elements analysed. Phenolic compounds generally did not increase in the attacked trees, questioning the suggestion of induction of phenolics following folivory attack and the anti-feeding properties of phenolics. Herbivory attack produced a general systemic shift in pines, in both primary and secondary metabolism, which was less intense and chemically different from the local responses. Local pine responses were similar between pine subspecies, while systemic responses were more distant.
Keywords: stromy; metabolomika; Metabolomics; plant-insect; Terpenes; Moths; býložravci; borovice lesní; systemic responses; metabolom; Trees; můry; Metabolome; terpeny; ženské pohlaví; Folivory; zvířata; phenolics; stoichiometry; metabolomics; Pinus sylvestris; Herbivory; Female; Animals